STUDI FITOKIMIA DAN FARMAKOLOGI BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) - Resha Rosalia; Devia Setyaningsih; Aghnia Ahda; Salma Aziz; Siti Lulu Luthfiah; Vera Dwi Apriani; Sri Tantia Dinita; Yuliani Dewi; Mira Oktaviani Malik (Jurnal Buana Farma, 2022)
At present, the existence of herbal medicines has succeeded in attracting global attention and many countries in the world are participating in conducting research on these herbal medicines. There are many diseases that can be looked for alternatives with compounds found in plants, including one of the Dayak Onion species (Eleutherine palmifolia (L.) Merr) which can be used as microbial agents, anti-inflammatory, antihypertensive, antidiabetic, antidermatophyte, anti-melanogenic and has anti-inflammatory activity. cytotoxic because of the content of flavonoids, alkaloids, saponins, tannins, steroids or triterpenoids, phenols, and quinones and their derivatives. There are many other uses of Onion Dayak which are only based on empirical experience. Therefore, further development in pharmacological research on Dayak Onions is needed to fulfill the medical interests of the general public.